Are Rising Athletics Allocations Associated with Student Costs: Evidence from Public NCAA Division I Universities (Higher Education Politics and Economics, 2020)
Many in the higher education community criticize the millions of dollars in financial allocations given to intercollegiate athletics departments by universities on the premise that when universities have to provide more allocation money to athletics, student costs increase.  Evidence supporting this argument, however, is largely anecdotal. This study used fixed effects regression analyses to explore whether year to year changes in university funds allocated to athletics lead to higher student costs. Our findings call into question the argument that rising athletics allocations are a significant direct driver of student costs.